Keyhole Approach for Clipping Anterior Circulation Aneurysms: Clinical Outcomes and Technical Note - Shao, Dongqi; Li, Yu; Sun, Zhixiang; Cai, Xintao; Zheng, Xialin; Jiang, Zhiquan (Frontiers in Surgery, 2021)
Purpose: Keyhole craniotomy is a minimally invasive approach for the treatment of anterior circulation aneurysm. In this study, we evaluated the benefits and value of the keyhole approach by analyzing the surgical results in 235 patients with anterior circulation aneurysm treated by the keyhole approach and identifying lessons learned from addressing various complications in this approach. Patients and Methods: This was a retrospective study in a single institution of 235 surgical patients with 248 anterior circulation aneurysms who had the supraorbital keyhole approach (SKA) or pterional keyhole approach (PKA) between January 2016 and January 2021. The modified Rankin Scale (mRS) was used to measure long-term results during follow up. Results: All 235 patients' aneurysms were fully clamped and have not recurred. Among them, 31 (13.2%) had intraoperative aneurysm rupture, 8 (3.4%) had cerebral vascular spasm, and 4 (1.7%) had intraoperative brain edema. There were seven (3.0%) cases of postoperative infection, eight (3.4%) cases of postoperative cerebral infarction, one (0.4%) case of postoperative hematoma, and two (0.8%) patients had some form of cognitive impairment after surgery. Follow up after surgery demonstrated that 189 out of the 235 patients (80.4%) had favorable outcomes (mRS score 0–2), and 43 (18.3%) had poor outcomes (mRS from 3–5). There were three deaths (1.28%). Conclusions: The keyhole approach has a quick postoperative recovery, a mild postoperative response, and a good surgical outcome. Our findings indicate that the keyhole approach is a safe and effective surgical method for the treatment of anterior circulation aneurysm.